2022
DOI: 10.3390/su14148636
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes of K–12 Schools’ Teachers in Serbia towards the Potential of Artificial Intelligence

Abstract: Similar to so many other aspects of modern life, education is gradually being automated by technological means. The software, apps, systems, platforms, and digital devices that permeate modern education are inextricably linked to these automated processes. One of the primary goals of automation has always been to improve quality and efficiency by reducing the number of human repetitive tasks based on machine learning (ML) algorithms and applications that facilitate the automation of decision-making of artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The findings suggest a positive connection between teachers’ awareness of GAI and their usage, aligning with the research of Kaplan-Rakowski and others in 2023. This correlation supports prior research emphasizing the link between teachers’ exposure to AI, their trust in the technology (as demonstrated by Nazaretsky et al (2022) ), and their willingness to incorporate AI into their teaching practices (as shown by Kuleto et al (2022) ). The findings also showed that most participants already contemplate specific AI applications (representing the understanding stage) or feel comfortable using AI (reflecting the familiarity stage), increasing awareness and utilization.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings suggest a positive connection between teachers’ awareness of GAI and their usage, aligning with the research of Kaplan-Rakowski and others in 2023. This correlation supports prior research emphasizing the link between teachers’ exposure to AI, their trust in the technology (as demonstrated by Nazaretsky et al (2022) ), and their willingness to incorporate AI into their teaching practices (as shown by Kuleto et al (2022) ). The findings also showed that most participants already contemplate specific AI applications (representing the understanding stage) or feel comfortable using AI (reflecting the familiarity stage), increasing awareness and utilization.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies emphasize the significance of gaining insights into teachers’ viewpoints regarding implementing emerging technologies ( Qahl & Sohaib, 2023 ), as exemplified by extended reality ( Kaplan-Rakowski et al, 2023 ) and virtual reality ( Kaplan-Rakowski, Dhimolea & Khukalenko, 2023 ). However, general artificial intelligence (GAI) integration has received limited attention in the literature, with a few exceptions ( Kuleto et al, 2022 ). Despite the increasing popularity and accessibility of GAI tools, which could be attributed to their relatively recent emergence, there remains a dearth of knowledge concerning teachers’ perceptions of integrating GAI, such as Chat GPT, into educational settings ( Celik et al, 2022 ; Wang, Liu & Tu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, teachers are afraid that AI system integration will depersonalize teaching approach and reduce social relationship with students. They believe that AI cannot perceive and provide socio-emotional support to learners (Kuleto et al, 2022). If young learners are obliged to interact with AI robot at nearly all learning activities, they will gradually lose learning ability of how to interact with respectable member of the society with empathy, reciprocity, which are the features of human relationships (Serholt et al, 2014).…”
Section: Social Knowledge and Skill Building Risksmentioning
confidence: 99%
“…While educators perceive the long-term viability of AI in ECE settings, they also emphasise the need for responsible and ethical use of AI. They stress the importance of balancing AI technologies and human interaction, play-based learning, and social-emotional development (Kuleto et al, 2022). Educators believe that integrating AI thoughtfully and purposefully can become a valuable resource that enhances, rather than replaces, the role of educators in ECE settings (Devi et al, 2022).…”
Section: Teachers Perceptions Of the Long-term Viability Of Ai In Ecementioning
confidence: 99%